On the periphery of HIV and AIDS: Reflections on stress as experienced by caregivers in a child residential care facility in South Africa - Kesh Mohangi; Chereen Pretorius (Taylor & Francis Group, 2017)
Few researchers have investigated how female caregivers of institutionalised children, especially those affected by HIV and AIDS, experience stress. The role played by caregivers cannot be overemphasised; yet caregivers who work in institutions caring for orphaned and/or abandoned children affected by HIV and AIDS, are often marginalised and on the periphery of the HIV and AIDS pandemic. The implication is that insufficient attention or consideration is given to the importance of the role they play in these children's lives. The objective of the study was to explore how female caregivers of institutionalised children affected by HIV and AIDS experience stress. A qualitative research project with a case study design was conducted. The purposively selected participants from a previously identified care facility were seven females in the age ranges of 35-59. Data was gathered during individual interviews and focus group discussions. Thematic content analysis of the data yielded the following themes: (1) contextualising caregiving as 'work'; (2) stresses linked to caregiving; and (3) coping with stress. Findings from this study indicated that participants experienced caregiving in an institution as stressful, demotivating, and emotionally burdensome. Moreover, caregivers working in an environment of HIV and AIDS experienced additional stress related to organisational and management impediments, lack of emotional and practical support, inadequate training, discipline difficulties, and lack of respect and appreciation from the children in their care. It is recommended that training and management support as well as personal support and counselling for caregivers in the institutional context could help them to cope better, feel empowered and to potentially elevate their status as valued members of society.